Mary Jiménez: Intimate and Universal - Bustamante, Emilio (2018)
The present article highlights peruvian filmmaker Mary Jiménez as a pioneer of the first person documentary in Latin America, and intents to prove that in her work there is an intention to meet with the Other and reintegrate the individual with the universe.